Analisis Kesalahan Siswa pada Soal Cerita Pecahan Menggunakan Tahapan Newman - Pera, Maria Agustina; Murniasih, Tatik Retno; Yuwono, Timbul (Jurnal Absis: Jurnal Pendidikan Matematika dan Matematika, 2021)
Students consider fractions to be complex material. The results of the dialogue on preliminary observations with a mathematics subject teacher at a junior high school in Malang showed that many students could not model problems in the form of mathematics. According to the Newman stage, this study aims to analyze students' mistakes in working on story questions about fractions. This type of research is descriptive qualitative research. A total of 23 students were given instruments in the form of 2 fraction test questions. Based on the test scores obtained, the students were categorized (high, medium, and low), and two subjects were selected for each category for the interview. They were checking the validity of the findings using the triangulation technique, namely, by comparing the results of direct observation, student test results, and interview data. Based on the research results, there were three biggest mistakes of the students: transformation errors, reading errors, and misunderstanding of the questions. Further research is recommended that students be given more story questions about solving fraction problems so that similar errors do not happen again